The Connection betweeen Unemployment and Migration at the Level of Hunedoara County and Town (European Journal of Marketing and Economics, 2024)
The population of Hunedoara County has manifested after the Revolution of December 1989 a continuous downward trend. According to National Statistics Institute in Hunedoara County, in 2012, at the last population census there was only a number of 418,545 people representing the constant population and since 2016 it had decreased with almost 5% in 4 years but counting from 1992 the decrease is of almost 28%. As far as concerns migration, the official figures of the number of the temporarily absent people left abroad for a shorter than a 12 months’ period it was 5,510 and the number of those who were left for a period longer than a year it was 15,215. As follows, the total numbe`r of migrants was 20,725 which represents a percentage higher than 4% from the total number of the population. Comparing the data received from the AJOFM Hunedoara (the statistics is effectuated every year in August) with those obtained from the CJRAE Hunedoara (statistics reported every year in February), - excepting the year 2015- when the effect of the liberalisation of the labour market in Great Britain can be remarked, it can be noticed a descendent evolution of the number of unemployed which fact drags a decrease of the children with migrant parents. On the other hand, a very important decline of the unemployment in 2017 resulted into a diminution of the parents who would leave abroad in the following year.
Keywords: migration, Hunedoara, statistics, number of unemployed, children who have migrant parents, school